Preoperative Computed Tomography Angiography Reveals Leaflet-Specific Calcification and Excursion Patterns in Aortic Stenosis. (December 2021) - Chen, Ian Y.; Vedula, Vijay; Malik, Sachin B.; Liang, Tie; Chang, Andrew Y.; Chung, Kieran S.; Sayed, Nazish; Tsao, Philip S.; Giacomini, John C.; Marsden, Alison L.; Wu, Joseph C.
Abstract : Background: Computed tomography–based evaluation of aortic stenosis (AS) by calcium scoring does not consider interleaflet differences in leaflet characteristics. Here, we sought to examine the functional implications of these differences. Methods: We retrospectively reviewed the computed tomography angiograms of 200 male patients with degenerative calcific AS undergoing transcatheter aortic valve replacement and 20 male patients with normal aortic valves. We compared the computed tomography angiography (CTA)-derived aortic valve leaflet calcification load (AVLCCTA ), appearance, and systolic leaflet excursion (LEsys ) of individual leaflets. We performed computer simulations of normal valves to investigate how interleaflet differences in LEsys affect aortic valve area. We used linear regression to identify predictors of leaflet-specific calcification in patients with AS. Results: In patients with AS, the noncoronary cusp (NCC) carried the greatest AVLCCTA (365.9 [237.3–595.4] Agatston unit), compared to the left coronary cusp (LCC, 278.5 [169.2–478.8] Agatston unit) and the right coronary cusp (RCC, 240.6 [137.3–439.0] Agatston unit; both P <0.001). However, LCC conferred the least LEsys (42.8° [38.8°–49.0°]) compared to NCC (44.8° [41.1°–49.78°], P =0.001) and RCC (47.7° [42.0°–52.3°], P <0.001) and was more often characterized as predominantly thickened (23.5%) compared to NCC (12.5%) and RCC (16.5%). Computer simulations of normal valves revealed greater reductions in aortic valve area following closures of NCC (−32.2 [−38.4 to −25.8]%) and RCC (−35.7 [−40.2 to −32.9]%) than LCC (−24.5 [−28.5 to −18.3]%; both P <0.001). By linear regression, the AVLCCTA of NCC and RCC, but not LCC, predicted LEsys (both P <0.001) in patients with AS. Both ostial occlusion and ostial height of the right coronary artery predicted AVLCCTA, RCC ( P =0.005 and P =0.001). Conclusions: In male patients, the AVLCCTA of NCC and RCC contribute more to AS than that of LCC. LCC's propensity for noncalcific leaflet thickening and worse LEsys, however, should not be underestimated when using calcium scores to assess AS severity. Abstract : Supplemental Digital Content is available in the text.